Využití metod termické analýzy ve výzkumu a vývoji léčiv - Seilerová, Lenka; Brusová, Hana; Kratochvíl, Bohumil; Krejčík, Lukáš (Chemické listy, 2012)
Thermal analysis is a valuable method in pharmaceutical research. A wide range of thermal methods are used in drug development like thermogravimetry (TG), diffe¬rential thermal analysis (DTA), differential scanning calori¬metry (DSC) and other sensitive and specific methods. The present review deals with application of these me¬thods in characterization of drugs and excipients, such as their polymorph stability, glass transition temperature, purity analysis and compatibility of drugs.
Keywords: Research; termické metody; Chemistry, Physical; Calorimetry, Differential Scanning; skelný přechod; výzkum; termografie; chemické techniky analytické; fyzikální chemie; diferenciální skenovací kalorimetrie; Pharmaceutical Preparations; farmaceutická technologie; léčivé přípravky; příprava léků; DSC; polymorfismus; Drug Compounding; kompatibilita; Thermogravimetry; Thermography; termogravimetrie; farmaceutický vývoj; Technology, Pharmaceutical; Chemistry Techniques, Analytical